PUNS IN ONE-LINER JOKES, BASED ON BIBLICAL STORIES - Giorgadze, Meri (Online Journal of Humanities ETAGTSU, 2016)
The present research deals with the study of the ways wordplay and humour are employed in onelinerjokes, using the example of humorous one-liners based on biblical stories. The data of the research are one-liner jokes containing puns, collected from different online sources. One of the main issues regarding the research lies in the difficulty of defining the methodology of the analysis of one-liner jokes. Another research question focuses on identifying specific features and classification of such jokes and their structural patterns. As is known, linguistic ambiguity forms a crucial element regarding the substantial proportion of jokes which also makes up the specific humorous effect. In order to build ambiguity, the fragment of the text must be capable of yielding two possible semantic interpretations. However, in a typical context-heavy environment achieving ambiguity is not a simple task. One-liner jokes, created on the basis of biblical stories are analysed from different perspectives, specifically from lexical, semantic and structural points of view. Full Text (PDF)